Evaluation of Indigenous Knowledge Systems of Traditional Rice Farmers in India - Binoo P. Bonny K. Vijayaragavan (Journal of Sustainable Agriculture,18:4,39 - 51 2001, 2001)
In recent years, especially in the context of sustainable agriculture, Indigenous Knowledge Systems (IKS), which deals with the farmers' adaptive strategies to the natural, physical and socio-economic environments of an agro-ecosystem, has gained prominence. In this paper, an attempt has been made to systematically document thelocal innovations of traditional rice farmers of the southern most part of India, Kerala. The thirty indigenous practices identified were documented by classifying them into rational and irrational practices based on the evaluation of a group of scientists and agricultural extension officials working in the area. The rational practices were again grouped as those which were evaluated through earlier, reported scientific works and those which had apparent rationality based on the existing scientific theory but needed further research to prove conclusively. It was striking to find that among the thirty resource conserving and risk reducing practices identified it was just to three practices that the scientists and extension officials could not attach any scientific rationality.